Enhancing the Survival Rate in Live Fish Transport by Utilizing Nanobubble Technology - Devkota, Hare Ram; Jha, Dilip Kumar; Joshi, Tista Prasai; Shrestha, Shreemat; Bhandari, Mahendra Prasad (Nepalese Journal of Aquaculture and Fisheries, 2023)
Efficient transportation of live fish is crucial for aquaculture, necessitating methods to ensure that fish maximize survival rates. This study was carried out in March 2022 at the Rainbow Trout Fishery Research Center to evaluate various aeration systems and packing methods for transporting trout fingerlings for 12 hours, with a focus on nanobubble technology. Closed and open transport systems were tested using oxygenated, ozonized, and air nanobubbles, compared to conventional methods. In the closed system with 500-750 fish per bag, ozone nanobubbles achieved significantly (P<0.05) higher survival rates of 99.6±0.10 and 99.3±0.0 %, versus 64.5% with conventional oxygen packing. The ozone nanobubbles extended the duration until the dissolved oxygen reached 4 mg/L. For open transportation, oxygen nanobubbles with a droplet size of around 100-600 nm led to 99.0±0.10% survival, significantly (P<0.05) exceeding 76.7±5.20% with regular oxygen aeration. Crucially, nanobubble systems consistently maintained elevated dissolved oxygen (8-9 mg/L) and reduced ammonia concentrations (0.01-0.03 mg/L), indicating superior fish survival during transport. The findings highlight the transformative potential in optimizing fish transport for sustainable aquaculture. Refinement of nanobubble packaging and aeration could significantly increase survival rates and efficiency, promoting sustainable aquaculture practices.